Ionic‐liquid‐impregnated resin for the microwave‐assisted solid–liquid extraction of triazine herbicides in honey. Issue 17 (24th July 2015) - Wu, Lijie; Song, Ying; Hu, Mingzhu; Yu, Cui; Zhang, Hanqi; Yu, Aimin; Ma, Qiang; Wang, Ziming
<x xml:space="preserve">Abstract</x> Microwave‐assisted ionic‐liquid‐impregnated resin solid–liquid extraction was developed for the extraction of triazine herbicides, including cyanazine, metribuzin, desmetryn, secbumeton, terbumeton, terbuthylazine, dimethametryn, and dipropetryn in honey samples. The ionic‐liquid‐impregnated resin was prepared by immobilizing 1‐hexyl‐3‐methylimidazolium hexafluorophosphate in the microspores of resin. The resin was used as the extraction adsorbent. The extraction and enrichment of analytes were performed in a single step. The extraction time can be shortened greatly with the help of microwave. The effects of experimental parameters including type of resin, type of ionic liquid, mass ratio of resin to ionic liquid, extraction time, amount of the impregnated resin, extraction temperature, salt concentration, and desorption conditions on the extraction efficiency, were investigated. A Box–Behnken design was applied to the selection of the experimental parameters. The recoveries were in the range of 80.1 to 103.4% and the relative standard deviations were lower than 6.8%. The present method was applied to the analysis of honey samples.